Analysis of Monetary and Fiscal Policy Mix in Encouraging Economic Recovery in Indonesia - Dwi Ananda; Wahyu Indah Sari; Lia Nazliana Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the impact of the monetary and fiscal policy mix on Indonesia's economic growth during the COVID-19 pandemic in the period 2013-2023. Using the Simultaneous Regression method (Two-Stage Least Squares/2SLS), this study tests two simultaneous equations, namely the effect of exports, unemployment rate, and inflation on economic growth (GDP), as well as the effect of exchange rates (exchange rates), interest rates, and GDP on inflation. The results of the study indicate that exports and unemployment have a significant negative effect on economic growth, while inflation has a significant positive effect on GDP. Meanwhile, the exchange rate and interest rate have a significant effect on inflation, but GDP does not have a significant effect on inflation. The normality test shows that the data is normally distributed and the autocorrelation test does not detect any autocorrelation, so the model used is valid. The effectiveness of monetary policy through the exchange rate channel on economic growth was found to be positive, although not statistically significant. This finding emphasizes the importance of coordination between fiscal and monetary policies, maintaining exchange rate stability, controlling inflation, and efforts to restore the real sector and reduce unemployment to support sustainable economic growth in Indonesia. This study provides recommendations for the government and monetary authorities to strengthen policy synergy in facing economic challenges, especially during times of crisis, to ensure more effective national economic stability and recovery.